¿Qué significa ayudar a la madurez? (Journal of Parents and Teachers, 2014)
The article presents the characteristics of human maturity. In this way, the author, through questions, answers questions related to how to help maturity, the elements of maturity, as well as the educational consequences of maturity. Finally, a questionnaire for families and teachers related to the acquisition of maturity is included.
Keywords: Parents School; Accompaniment; Maturity; Families